2017
DOI: 10.1080/1461670x.2017.1377102
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of Politicians’ Perceptions of the News Media

Abstract: There is limited knowledge about why political actors are dissatisfied with journalism. This article attempts to answer this question by pointing to individual-level perceptual processes of politicians. We argue that part of politicians' unease with the media can be explained by the hostile media phenomenon (HMP). Originally developed in audience research, the HMP refers to a process by which highly involved individuals tend to perceive media coverage as biased against their own views. Based on a survey of pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 43 publications
3
17
0
2
Order By: Relevance
“…In their seminal study, Cohen et al (2008) found that perceptions of Israeli parliamentarians about media power positively affect their efforts to achieve media coverage. Matthes et al (2019) found a similar connection between perceptions and media behaviour. They showed that MPs (from Switzerland, Germany and Austria) who have more hostile perceptions of the media have less contacts with journalists.…”
Section: Rq1: To What Extent Is the Strategic Media Behaviour Of Politicians Connected To Their Perceptions Of Media Importance?supporting
confidence: 52%
See 1 more Smart Citation
“…In their seminal study, Cohen et al (2008) found that perceptions of Israeli parliamentarians about media power positively affect their efforts to achieve media coverage. Matthes et al (2019) found a similar connection between perceptions and media behaviour. They showed that MPs (from Switzerland, Germany and Austria) who have more hostile perceptions of the media have less contacts with journalists.…”
Section: Rq1: To What Extent Is the Strategic Media Behaviour Of Politicians Connected To Their Perceptions Of Media Importance?supporting
confidence: 52%
“…Lengauer, Donges and Plasser 2014;Van Aelst and Walgrave 2011). However, the extent to which these perceptions are linked to their behaviour is much less clear (Cohen, Tsfati and Sheafer 2008;Matthes, Maurer and Arendt 2019). The second question focuses on the link between politicians' communication behaviour and media success: To what extent is strategic media behaviour connected to media appearances?…”
Section: Introductionmentioning
confidence: 99%
“…This delegitimization impedes the public function of journalism, the nature of political discourse, and the democratic process in general (e.g. Matthes, Maurer, & Arendt, 2019;Pfetsch, 2004;Tsfati, 2014). This increasing political antagonism is also likely to have a direct effect on journalists' work.…”
Section: Empirical Evidence On the Fake News Genrementioning
confidence: 99%
“…As Epstein (, pp. 122–123) put it, media gatekeeping “involves choosing and ordering the significant aspects of the data collected … some statements might be emphasized and highlighted; others, played down or omitted entirely.” Given the existence of such a media slant or bias, politicians who perceive media contents as “hostile” (i.e., biased against their own views) would be less likely to contact journalists to deliver their messages (Matthes, Maurer, & Arendt, ). It therefore follows that politicians whose ideological positions differ from the positions of news media would be more likely to rely on social media technologies.…”
Section: Introductionmentioning
confidence: 99%